2023
DOI: 10.3390/ma16072864
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Formation, Characterization, and Oxidative Catalytic Valorization of Humins

Abstract: The industrial use of biomass, e.g., for the production of platform chemicals such as levulinic acid, became increasingly important in recent years. However, the efficiency of these processes was reduced by the formation of insoluble solid waste products called humins. Herein, the formation of humins from various carbohydrates was investigated under different process conditions, in order to obtain information about the structure and the formation mechanism. During this process, new potential structural fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 51 publications
4
20
0
Order By: Relevance
“…Both linkages via C–O–C and C–C bonds are plausible and coexistence in the real humin structure cannot be excluded either. An exemplary structural motif that allows both types of bonds was recently suggested by Wassenberg et al and corroborated via mass spectroscopic analyses (Table , entry 5). Nevertheless, we can conclude that the complex structure of humins has not been fully elucidated to date.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Both linkages via C–O–C and C–C bonds are plausible and coexistence in the real humin structure cannot be excluded either. An exemplary structural motif that allows both types of bonds was recently suggested by Wassenberg et al and corroborated via mass spectroscopic analyses (Table , entry 5). Nevertheless, we can conclude that the complex structure of humins has not been fully elucidated to date.…”
Section: Introductionmentioning
confidence: 58%
“…As mentioned and discussed above as well as supported by a large number of studies, the humin structure exists of a furan-rich polymer network. ,,,,,, Numerous results indicate a linkage of these furan rings via oxygen-functionalized C–O–C bonds. ,,,, However, aliphatic C–C bonds are also under discussion. ,,, Hoang et al and Shi et al suggest that the furan rings are also linked via aliphatic acetyl groups as well as via CH 2 bonds. Both linkages via C–O–C and C–C bonds are plausible and coexistence in the real humin structure cannot be excluded either.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…5,14,19,20 Another promising idea is the chemical valorization of humins by catalytic oxidation. 5,21 Pioneering work in this field was done by Maerten et al , 5 who demonstrated for the first time the chemical valorization of humins by selective catalytic oxidation (SCO) using polyoxometalate (POM) catalysts to short-chain carboxylic acids. POMs are a unique class of inorganic compounds having a wide variety of geometric and electronic structural properties.…”
mentioning
confidence: 99%